Inflammation as a Driver of Clonal Evolution in Myeloproliferative Neoplasm - Angela G. Fleischman (Mediators of Inflammation)
Our understanding of inflammation’s role in the pathogenesis of myeloproliferative neoplasm (MPN) is evolving. The impact of chronic inflammation, a characteristic feature of MPN, likely goes far beyond its role as a driver of constitutional symptoms. An inflammatory response to the neoplastic clone may be responsible for some pathologic aspects of MPN. Moreover, JAK2V617F mutated hematopoietic stem and progenitor cells are resistant to inflammation, and this gives the neoplastic clone a selective advantage allowing for its clonal expansion. Because inflammation plays a central role in MPN inflammation is a logical therapeutic target in MPN.